Do Patients Reporting Fractures Experience Food Insecurity More Frequently Than the General Population?. Issue 5 (13th May 2023) - Jella, Tarun K.; Cwalina, Thomas B.; Schmidt, Jenna E.; Wu, Victoria S.; Yong, Taylor M.; Vallier, Heather A.
Abstract: Background: The economic burden of traumatic injuries forces families into difficult tradeoffs between healthcare and nutrition, particularly among those with a low income. However, the epidemiology of food insecurity among individuals reporting having experienced fractures is not well understood. Questions/purposes: (1) Do individuals in the National Health Interview Survey reporting having experienced fractures also report food insecurity more frequently than individuals in the general population? (2) Are specific factors associated with a higher risk of food insecurity in patients with fractures? Methods: This retrospective, cross-sectional analysis of the National Health Interview Survey was conducted to identify patients who reported a fracture within 3 months before survey completion. The National Health Interview Survey is an annual serial, cross-sectional survey administered by the United States Centers for Disease Control, involving approximately 90, 000 individuals across 35, 000 American households. The survey is designed to be generalizable to the civilian, noninstitutionalized United States population and is therefore well suited to evaluate longitudinal trends in physical, economic, and psychosocial health factors nationwide. We analyzed data from 2011 to 2017 and identified 1399 individuals who reported sustaining a fracture during the 3 months preceding their survey response. Among these patients, 27% (384 of 1399) were older than 65 years, 77% (1074) were White, 57% (796) were women, and 14% (191) were uninsured. A raw score compiled from 10 food security questions developed by the United States Department of Agriculture was used to determine the odds of 30-day food insecurity for each patient. A multivariate logistic regression analysis was performed to determine factors associated with food insecurity among patients reporting fractures. In the overall sample of National Health Interview Survey respondents, approximately 0.6% (1399 of 239, 168) reported a fracture. Results: Overall, 17% (241 of 1399) of individuals reporting broken bones or fractures in the National Health Interview Survey also reported food insecurity. Individuals reporting fractures were more likely to report food insecurity if they also were aged between 45 and 64 years (adjusted odds ratio 4.0 [95% confidence interval 2.1 to 7.6]; p < 0.001), had a household income below USD 49, 716 (200% of the federal poverty level) per year (adjusted OR 3.1 [95% CI 1.9 to 5.1]; p < 0.001), were current tobacco smokers (adjusted OR 2.8 [95% CI 1.6 to 5.1]; p < 0.001), and were of Black race (adjusted OR 1.9 [95% CI 1.1 to 3.4]; p = 0.02). Conclusion: Among patients with fractures, food insecurity screening and routine nutritional assessments may help to direct financially vulnerable patients toward available community resources. Such screening programs may improve adherence to nutritional recommendations in the trauma recovery period and improve the physiologic environment for adequate soft tissue and bone healing. Future research may benefit from the inclusion of clinical nutritional data, a broader representation of high-energy injuries, and a prospective study design to evaluate cost-efficient avenues for food insecurity interventions in the context of locally available social services networks. Level of Evidence: Level III, prognostic study.